Effects of Wi-fi Radiation in Ex Vivo Immature Rat Seminiferous Tubules Oxidative Stress - Peixoto, Rita Alexandra Van Der Sandt (2017)
Approximately 15% of couples globally of reproductive age fail to accomplish pregnancy within a year of unprotected intercourse, accounting the male factor approximately 50% of the cases. Over the years male fertility has been decreasing being associated with numerous factors such as lifestyle, tobacco, alcohol and chemicals. However, with technological evolution, another factor has been pointed as an important contributor to infertility: the electromagnetic radiation (EMR) from mobile devices such as mobile phones, tablets and computers. Although there are several studies correlating the EMR and negative effects on male fertility, including the increase in oxidative stress, none of those studies used a realistic model of EMR exposure. Thus, our goal was to build a realistic model of EMR exposure and use it to shed light in the association between EMR from wi-fi devices and male (in)fertility, highlighting oxidative stress and apoptosis. Therefore, firstly we developed the EMR exposure model through 3 instruments: a Wi-fi module (information transmission network), a mbed (programming module of information packets) and a wifly (reception and emissor antenna for information packets). After the development of the exposure model, we proceeded to the validation through the exposure of 3-month-old Wister rat spermatozoa for the time frame of 1h and evaluated the sperm parameters (motility, morphology and viability). Spermatozoa exposure to 2.4GHz of radiation lead to a statistically significant difference in the motility with a 2.4-fold difference, however, there wasn’t a statistically significant difference in the other parameters. Secondly, we proceeded to the selection of the ideal animals age for the present project to study EMR influences through a histological cell population study of the testis of 4 different ages: 19, 20, 21 and 22 days. As the goal of this work was to study animals in the final stages of development and maturation of SCs and in an early development of germ cells, Wistar rats with 20 days were selected. Thus, two groups of ex vivo immature rats (20 days) seminiferous tubules culture (control and exposed) were exposed to 2.4GHz radiation by the created model for 72h, TOS concentrations and Caspase 3 activity were measured. Immature rats Set exposure to our model resulted in statistically significant differences in both TOS concentration and Caspase 3 activity, with a 2-fold difference in the exposed group compared with control group in TOS concentration while Caspase 3 activity had a 1.6-fold difference. Thus, was possible to conclude through motility results that the developed model is effective in the transmission of EMR, simulating the daily use of diverse equipment existing in the present in our homes. Also, the increased in TOS concentration and Caspase 3 activity supports the hypothesis of the use of these technologies being harmful to male fertility thus being a factor to be taken into consideration in the evaluation of male fertility.